2008
DOI: 10.17221/8/2008-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the HMW- and LMW-glutenin subunits and SDS-sedimentation volume in Spanish hulled wheat lines

Abstract: Emmer and spelt are two hulled wheats that were widely grown in Spain until the latter 1960s. Twentynine emmer and twenty-six spelt lines obtained from Spanish accessions of these hulled wheats were analysed for quality traits and endosperm storage protein composition. The results showed a wide range of variability in these traits. Likewise, a certain association between some alleles of these proteins and the SDS-sedimentation volume has been detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Quantitative trait loci with large effects are very useful for trait improvement via marker-assisted selection. However, molecular markers linked to quantitative trait loci are being routinely developed using materials derived from bi-parental crosses such as F2, recombinant inbred lines (RILs), and double haploid (DH) populations on limited genetic backgrounds and covering only a few meiotic events (Caballero et al 2008). In fact, the effectiveness of molecular markers needs to be validated by determining the target phenotype in independent populations and different genetic backgrounds; this is referred to as marker validation (Sharp et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci with large effects are very useful for trait improvement via marker-assisted selection. However, molecular markers linked to quantitative trait loci are being routinely developed using materials derived from bi-parental crosses such as F2, recombinant inbred lines (RILs), and double haploid (DH) populations on limited genetic backgrounds and covering only a few meiotic events (Caballero et al 2008). In fact, the effectiveness of molecular markers needs to be validated by determining the target phenotype in independent populations and different genetic backgrounds; this is referred to as marker validation (Sharp et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Caballero et al (2001Caballero et al ( , 2004a found considerable variability between seed storage proteins in the Spanish spelt collection. Some of these allelic variants showed an association with high gluten strength (Caballero et al, 2008b). Another important aspect, the starch quality, has also been analysed in this collection through polymorphism assessment of waxy proteins by SDS -PAGE (Guzman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The ST and SV are parameters highly influenced by the protein compositions, i.e., glutenins and gliadins, their fractions, the ratio between them as well as the total protein content ( Payne et al, 1988 ; Deng et al, 2006 ; Rogers et al, 2006 ; Caballero et al, 2008 ; Dhaka and Khatkar, 2015 ). Some genes have been cloned in controlling the protein compositions, high molecular weight glutenin subunits (HMW-GS; Thompson et al, 1985 ; Anderson and Greene, 1989 ), low molecular weight glutenin subunits (LMW-GS) ( D’Ovidio et al, 1992 ; Ikeda et al, 2002 ), and gliadin ( Rafalski et al, 1984 ; Sugiyama et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%